AZA OLMAYAN GİREMEZ:_x000D_ TÜRKİYE'DE SİVİL TOPLUM VE SİVİL TOPLUM KURULUŞLARININ_x000D_ BEYAZ PERDEYE YANSIMALARI - TAYŞİR, EYÜP AYGÜN (My University, 2019)
Bu çalışma, Türkiye'de sivil toplum ve sivil toplumun örgütlenme biçimlerinden biri olan sivil toplumkuruluşlarının güncel görünümünü, bahsi geçen kavramların 2000 sonrası Türkiye sinemasına yansımalarıüzerinden yorumlamayı amaçlamaktadır. Bu bağlamda, çalışmada 2000 sonrası Türkiye sinemasından sekizfilm göstergebilimsel yöntem yardımıyla incelenmiş ve sivil toplum ve sivil toplum kuruşlarının filmlerdekiyansımaları araştırmacılar tarafından sivil toplum ve sivil toplum kuruluşları yazınlarıyla ilişkilendirilerekyorumlanmaya çalışılmıştır

This study aims to analyze the current situation of civil society and one of its organized forms, nongovernmental organizations, in Turkey through their reflections to Turkish cinema movies that were shot after_x000D_ the year 2000. In this context, in this study, eight movies from Turkey were analyzed by using semiology_x000D_ method. Reflections of the concepts of civil society and non-governmental organizations in these movies were_x000D_ interpreted by relating them to civil society and non-governmental organizations literatures.
Non-members are not Allowed: Civil Society and Non-Governmental Organizations and their Reflections to the Screen in Turkey